CCR4-positive peripheral T-cell lymphoma presenting as eosinophilic pneumonia and developing from prolonged pustular psoriasis. Issue 2 (February 2021) - Sekiguchi, Nodoka; Komatsu, Masamichi; Ichiyama, Takashi; Kobayashi, Aya; Gomi, Daisuke; Fukushima, Toshirou; Kobayashi, Takashi; Noguchi, Takuro; Nakazawa, Hideyuki; Asano, Naoko; Ishida, Fumihiro; Koizumi, Tomonobu
A 29-year-old woman with chronic, prolonged pustular psoriasis was admitted to our hospital because of high-grade fever and a systemic skin rash. General examination revealed a whole-body skin rash and superficial lymphadenopathy. Peripheral blood examination showed unclassified cells positive for CD3, CD4, and T-cell receptor αβ, and negative for CD20 and CD56. Soon after administration, she developed acute respiratory failure and required artificial ventilation. Bronchoalveolar lavage fluid showed increased numbers of eosinophils and abnormal lymphocytes of the same phenotype in peripheral blood and skin. She was diagnosed with eosinophilic pneumonia, and her respiratory failure was improved by corticosteroid therapy. Based on the histological findings of skin, lymph node, and bone marrow biopsies, a diagnosis of peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), with positivity for CC chemokine receptor 4 was made. She received chemotherapy followed by allogeneic stem cell transplantation, which resulted in complete remission of her PTCL-NOS. She remained alive and disease-free 6 years later. This is the first reported case of PTCL-NOS developing during the clinical course of pustular psoriasis. The clinical manifestations of PTCL-NOS are complex, but an accurate diagnosis and appropriate therapy may produce a good clinical outcome in patients with PTCL-NOS.